STRATEGI PEMASARAN UMKM MELALUI OPTIMALISASI PENERAPAN BRANDING PRODUK DAN DIGITAL MARKETING: UMKM KAKAPALAN DI DESA CIKAKAK, SUKABUMI - Pradesa, Kohar; Hopeman, Teofilus Ardian; Cahyana, Wahyudi; Alfiani, Isma; Elfariani, Rahma; Oktasyah, Rivan; Suwandi, Zakia Maulida (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
This Community Service activity in Cikakak village is moving through the SINARAKSA Program (Village Wisdom-Based MSME Empowerment) which aims to optimize the importance of product branding and digital marketing for craft SMEs in Cikakak village, Sukabumi district. This community service activity aims to provide information about the importance of implementing product branding and digital marketing to one of the MSME partners engaged in shipping. The approach taken in implementing this activity is through training and mentoring to one partner, namely Ms. Acih's Kakapalan MSME. This activity was carried out through three stages, namely pre-activity, preparation, and implementation. The results of this activity include creating a logo as a product brand identity and creating an account on the Shopee platform as a means of selling partner products. With social media accounts, the quality of post content and logos becomes more attractive to consumers. In addition, this activity also contributes to increasing partners' understanding of adaptation strategies in the digital era